2005
DOI: 10.1097/01.hjh.0000163156.37363.47
|View full text |Cite
|
Sign up to set email alerts
|

Thiazide diuretics enhance nocturnal blood pressure fall and reduce proteinuria in immunoglobulin A nephropathy treated with angiotensin II modulators

Abstract: Diuretics enhanced nocturnal BP decline and reduced urinary protein excretion in patients with IgA nephropathy treated with angiotensin II modulators. The combination of angiotensin II modulators and diuretics may have additional therapeutic advantages in relieving the renal and cardiovascular risks by reducing nocturnal high blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
40
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 27 publications
0
40
0
1
Order By: Relevance
“…These results are consistent with the fact that the combination of thiazide diuretics and RAS inhibitors has been used to lower blood pressure and limit target-organ damage. 43,44 We acknowledge a limitation that the indirect tail-cuff method used to determine SBP is not adequate for ruling out the possibility that the results could be attributable to differences in blood pressure between the different treatment groups. 45 We also acknowledge that the use of anesthetics ketamine and xylazine may have affected some of our results including measurements of the RAS, because those agents may stimulate sympathetic nervous system in the rats.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the fact that the combination of thiazide diuretics and RAS inhibitors has been used to lower blood pressure and limit target-organ damage. 43,44 We acknowledge a limitation that the indirect tail-cuff method used to determine SBP is not adequate for ruling out the possibility that the results could be attributable to differences in blood pressure between the different treatment groups. 45 We also acknowledge that the use of anesthetics ketamine and xylazine may have affected some of our results including measurements of the RAS, because those agents may stimulate sympathetic nervous system in the rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is as yet unknown whether this narrowing of PP induced by dual blockade of the renin-angiotensin system will translate into a long-term reduction in microvascular complications. Several researchers have demonstrated that it is possible to restore the normal circadian BP pattern in 'non-dipper's with selective antihypertensive therapy directed towards an elevated night BP [37][38][39][40]. Interestingly, this approach has been reported to reduce 24 h albumin excretion rate in microalbuminuric patients with essential hypertension, thus suggesting an increased organoprotective effect of reestablishing the normal diurnal BP rhythm [39].…”
Section: Discussionmentioning
confidence: 99%
“…22 Much as in our previous reports, 23 our present patients with high baseline ANP and BNP levels were likely to have a high night-time systolic BP level, which strengthens the previous findings that persistent intravascular volume Table 4. Association between the change of BP, haemostasis, biochemical, and cardiovascular parameters before and after eplerenone treatment (n = 20) expansion is an important cause of uncontrolled BP, 24 and particularly uncontrolled night-time BP levels, 25 in hypertensive patients treated with anti-hypertensive agents that included ACEIs and ARBs 26 ; eplerenone may represent a more reasonable approach in such cases. However, in the present study, no significant differences were found in body weight, serum potassium level, or serum uric acid level between before and after eplerenone treatment.…”
Section: Discussionmentioning
confidence: 99%